2011
DOI: 10.1016/j.neuroimage.2010.12.008
|View full text |Cite
|
Sign up to set email alerts
|

DTI measures in crossing-fibre areas: Increased diffusion anisotropy reveals early white matter alteration in MCI and mild Alzheimer's disease

Abstract: Though mild cognitive impairment is an intermediate clinical state between healthy aging and Alzheimer's disease (AD), there are very few whole-brain voxel-wise diffusion MRI studies directly comparing changes in healthy control, mild cognitive impairment (MCI) and AD subjects. Here we report whole-brain findings from a comprehensive study of diffusion tensor indices and probabilistic tractography obtained in a very large population of healthy controls, MCI and probable AD subjects. As expected from the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
394
3
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(449 citation statements)
references
References 59 publications
48
394
3
4
Order By: Relevance
“…Compared with other imaging techniques, DTI is more sensitive because it can detect WM microstructural changes well before a macrostructural loss of WM becomes measurable by other procedures, such as voxel-based morphometry. 19 Although the precise underlying mechanism for the changes of anisotropy is still unclear, decreased FA or increased RD may be interpreted as loss or insufficient development of myelination, loss of axons, gliosis, or tissue edema. Taking into account that our prelingually deaf adolescents did not show any pathologic changes as a result of brain injury, we can ascertain that the anisotropy changes may best be attributed to axonal loss and/or lack of myelination at an early age in life.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other imaging techniques, DTI is more sensitive because it can detect WM microstructural changes well before a macrostructural loss of WM becomes measurable by other procedures, such as voxel-based morphometry. 19 Although the precise underlying mechanism for the changes of anisotropy is still unclear, decreased FA or increased RD may be interpreted as loss or insufficient development of myelination, loss of axons, gliosis, or tissue edema. Taking into account that our prelingually deaf adolescents did not show any pathologic changes as a result of brain injury, we can ascertain that the anisotropy changes may best be attributed to axonal loss and/or lack of myelination at an early age in life.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study including both AD and MCI subjects [196] demonstrated a circumscribed increase in FA. These findings were aided by examining variations of a third tensor invariant, tensor mode [197] allowing to differentiate the type of anisotropy (planar, e.g.…”
Section: Diffusion Tensor Imagingmentioning
confidence: 94%
“…1). Notably, this mask did not include the superior longitudinal fasciculus, located medial to S1-adjacent U-fibres, as it is difficult to interpret fractional anisotropy in crossing-fibre areas (Douaud et al, 2011).…”
Section: Mri Outcomes S1 Cortical Mapping With Functional Mrimentioning
confidence: 99%